Legal and Ethical Aspects of Informed Consent in BPJS Health Emergency Services - Anna Veronica Pont; Ta'adi; Muchamad Taufiq; Ady Purwoto; Mawardi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Informed consent is a crucial element in the healthcare system as it ensures that patients provide consent based on a sufficient understanding of the medical procedures to be performed. In the context of emergency services, where patients often present with critical conditions requiring immediate action, the implementation of informed consent becomes more complex. BPJS Kesehatan, as the provider of healthcare services for the public, holds the responsibility to ensure that medical treatments within their network respect patient rights, both legally and ethically. This article aims to explore in-depth the legal and ethical aspects of implementing informed consent in emergency healthcare services under the BPJS Kesehatan program.